Pengaruh Self-Esteem dan Motivasi Berprestasi terhadap Kepuasan Kerja Guru SMK Negeri di Wilayah Jakarta Selatan - Yun Risnawati (LPPM STKIP Kusuma Negara, 2018)
The objective of the research is to obtain information about the effect of self-esteem and achievement on job satisfaction on teacher of vocational high school. The research was conducted to all of vocational high schools in south Jakarta by using a survey method with path analysis applied in testing hypothesis. The number 225 teachers as sample was selected by using slovin formula. The research conclude: (1) there is direct effect of self-esteem on job satisfaction. (2) there is direct effect of achievement on job satisfaction. (3) there is direct effect self-esteem on achievemet. Therefore to enhance teacher’s job satisfaction can be carried out by self-esteem, and achievement.